Clusters as Innovation Engines: The Accelerating Strengths of Proximity - Ferras, Xavier; Nylund, Petra (European Management Review, 2019)
As economic competition is becoming global, innovation clusters emerge as a salient level of competitive analysis. We hence study when and how innovation clusters strengthen innovation at firm level. We review insights in this topic from different theoretical perspectives, for example, neoclassical economics, evolutionary economics, behavioral economics, strategic management and open innovation, in search of a comprehensive theoretical framework that explains the relationship between firm innovation and the concentration of innovative activities in the proximity. We then deduce five strengths which drive technological change in innovation clusters, namely attraction, information, interaction, anticipation, and rivalry. The model has implications for researchers, managers, and policymakers and contributes to our understanding of the acceleration of innovation within clusters.
Keywords: innovation clusters; innovation ecosystems; proximity; attraction; interaction; anticipation